2008
DOI: 10.3354/dao01961
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of iridovirus from freshwater ornamental fish (pearl gourami) to marine fish (rock bream)

Abstract: Freshwater pearl gourami Trichogaster leeri and seawater rock bream Oplegnathus fasciatus infected by the iridoviruses PGIV-SP and IVS-1 were carrying similar numbers of viral particles (2.52 × 10 8 and 2.46 × 10 8 viral genome copies mg -1 spleen tissue, respectively). The viral genome copy number for both iridoviruses decreased much faster in seawater than in freshwater, reaching a concentration of less than 0.5%, versus 26 to 54% in freshwater, after 4 d of incubation at 25°C. The decrease in copy number al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
(38 reference statements)
0
20
0
1
Order By: Relevance
“…This is the first report of ISKNV-like megalocytivirus in Kissing gourami. Megalocytivirus was also detected in Red tiger oscar (Astronotus ocellatus), Blue ram (Microgeophagus ramirezi), Guppy, Platy, molly (Poecilia sphenops and Poecilia latipinna) and Angelfish, all belonging to families of freshwater ornamental fish species in which megalocytivirus has previously been detected or suspected (Nolan et al, 2015;Stephens et al, 2009;Whittington et al, 2009;Jeong et al, 2008a;Jeong et al, 2008b;Lewis and Leong, 2004;Paperna et al, 2001). The majority of apparently healthy fish that were qPCR-positive had low viral loads.…”
Section: Tablementioning
confidence: 87%
“…This is the first report of ISKNV-like megalocytivirus in Kissing gourami. Megalocytivirus was also detected in Red tiger oscar (Astronotus ocellatus), Blue ram (Microgeophagus ramirezi), Guppy, Platy, molly (Poecilia sphenops and Poecilia latipinna) and Angelfish, all belonging to families of freshwater ornamental fish species in which megalocytivirus has previously been detected or suspected (Nolan et al, 2015;Stephens et al, 2009;Whittington et al, 2009;Jeong et al, 2008a;Jeong et al, 2008b;Lewis and Leong, 2004;Paperna et al, 2001). The majority of apparently healthy fish that were qPCR-positive had low viral loads.…”
Section: Tablementioning
confidence: 87%
“…In China, a recent molecular epidemiology study indicated that over 50 cultured and wild marine fish species could be hosts of ISKNV‐like viruses in the South China Sea (Wang et al., ). In Korea, both clinical and asymptomatic infections by ISKNV‐like megalocytiviruses were reported in 10 freshwater ornamental fish species (Jeong et al., ). These results indicate that megalocytiviruses have become one of the most important causative agents of fish diseases (cited by Dong et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The often unrestricted relationship between the pet trade and research colonies undoubtedly facilitates the introduction of viral pathogens, as well as parasites and bacteria, into laboratory zebrafish colonies. Although knowledge of the viruses that infect the aquarium fish species that are raised with zebrafish in the pet trade is limited, the viruses that have been described include herpesviruses (Gilad et al 2002; Jeffery et al 2007), iridoviruses (Go et al 2006; Hossain et al 2008; Jeong et al 2008a,b), a nodavirus (Hegde et al 2003), and a reovirus (Seng et al 2004). This research not only demonstrates that laboratory zebrafish may still harbor a variety of pathogens from their origin in the pet trade but also provides evidence that zebrafish raised in outdoor ponds continue to directly enter laboratory colonies, providing a constant source of new pathogens from other pet and aquarium species.…”
Section: Importance Of Biosecurity For Laboratory Zebrafishmentioning
confidence: 99%